PELATIHAN DAN PENDAMPINGAN PENGELOLAAN PAKAN MANDIRI SEBAGAI UPAYA PENINGKATAN PRODUKSI BUDIDAYA DI DESA GUNUNGPRING, KECAMATAN MUNTILAN, KABUPATEN MAGELANG - Hidayati, Sri; Armando, Eric; W, Tri Sumarni; Pramono, Pradipta Bayuaji; Sari, Annisa Novita; Waluyo, Waluyo; Azril, Muh; Silmi Qori Tartila, Shobrina (Fakultas Pertanian_Universitas Tidar, 2022)
Feed is one of the main components with important function to support the freshwater fish culture success. Sufficient feed quantity and quality can ensure the fish culture cycle continuity. Feed occupies the highest position, which spends 60-80% of the total production cost requirement in intensive fish culture to support the fish growth. The high feed cost is unmatched with the fish selling price, resulting in a minimum profit gain. Based on this condition, a community service, focusing on self-produced feed training needs to be implemented to increase the cost efficiency and effectiveness in freshwater fish culture. This training was conducted in Gunungpring Village, Muntilan Sub-district, Magelang District with fish cultivator communities. The feed used as the object for this training contained artificial and live feed. Training activities contained surveys, field observations, outreach, counseling, mentoring, monitoring, and evaluation. This training could clearly introduce the community to the use of alternative feeds for ornamental and consumed-fish commodities. Live feed production training included Azolla sp., Daphnia sp., silkworms, and earthworms, while artificial feed included pellets of pf500-1000. This training program increases the community understanding and skills, followed by the quality and quantity of fishery products. As the training also has an impact on the regional food security with massive community assistance, so harvest failure can be minimized optimally.